Social Adaptation in Context: The Differential Role of Religiosity and Self-Esteem in Vulnerable vs. Non-vulnerable Populations – A Registered Report Study - Neely-Prado, Alejandra; van Elk, Michiel; Navarrete, Gorka; Hola, Fernanda; Huepe, David (Frontiers in Psychology, 2021)
There is evidence that religiosity and self-esteem are positively related, while self-esteem and religiosity in turn predict successful social adaptation. Moreover, self-esteem has been shown to be directly related to social adaptation in vulnerable contexts. In this registered report study we tested the hypothesis that religiosity has a positive influence on social adaptation for people living in vulnerable contexts and that self-esteem is a mediator of this relationship. Evidence from this study indicates that there is no effect of religiosity on social adaptation nor on self-esteem, independent of whether people live in vulnerable contexts or not.